Rekonstruksi Pemikiran Sufi Kontemporer: Analisis Pemikiran Jalaluddin Rumi dalam Konteks Globalisasi - Kasanova, Ria; Mohammad Rudiyanto (CV Kalimasada Group, 2025)
This article analyses the reconstruction of Jalaluddin Rumi's thought in the context of globalisation to understand how his teachings adapt to contemporary dynamics. Rumi, as an important figure in the Sufi tradition, offers concepts such as universal love, existential unity, and mystical experience that have been translated and presented in various formats for a global audience. This research shows that globalisation has enabled the wide dissemination of Rumi's teachings through digital media and integration with modern spiritual practices, but also poses challenges regarding the preservation of the authenticity of the teachings. The findings show that despite the risk of distortion, Rumi's teachings remain relevant and influential in an increasingly connected world. This article recommends further research into how Sufi thought is adapted and sustained in various cultural contexts, as well as the impact of globalisation on the integrity of the teachings.